Copper oxide nanoparticles induce oxidative stress, DNA strand breaks and laccase activity in aquatic fungi - Pradhan, Arunava (2011)
This work was supported by the DAAD-FCT-2010-2011 project (Micro)analysis of nanoparticles on aquatic fungi and A. Pradhan received the FCT grant SFRH/BD/45614/2008.